The kindness revolution : the company-wide culture shift that inspires phenomenal customer service - Horrell, Edward (AMACOM, 2006)
Despite years of focus on the importance of customer service, most businesses still have a lot to learn. Too many merely tweak a script, roll out a new offer, then disappear from the scene, leaving their frontline staff - often underpaid and badly overworked - to expertly, cheerfully handle all the real-life encounters with real-life customers who can make or break a company. That's no way to run a business, says customer service expert Ed Horrell. If you treat your frontline employees with indifference or disregard, you can expect them to treat your customers with indifference - and you can then expect to have indifferent customers who will drop you for the next best thing without a murmur of regret. Combining extensive research with inspiring real-life examples from companies known for their outstanding customer service - such as L.L. Bean, Chick-fil-A, Nordstrom, Mrs. Fields, St. Jude Children's Research Center, The Ritz-Carlton, FedEx, and more - Horrell explains in The Kindness Revolution that providing exceptional, compassionate customer service can only happen when you build a deep and lasting relationship with your employees. And it is kindness, says Horrell, that most characterizes that relationship. For organizations large and small, of any size or industry, The Kindness Revolution is a resounding wake-up call to change the way your company thinks about its employees, and to practice the basic values of dignity, respect, courtesy, and kindness from top to bottom throughout your organization. The way you treat your employees will be the way they treat your customers. Follow the wise advice and insightful examples in The Kindness Revolution, and experience the enormous payback in loyal customers, a more prosperous company - and a better way of life.